Kuroshio intrusion into the South China Sea: A review - Nan, Feng; Xue, Huijie; Yu, Fei (Progress in oceanography, 2015)
•Past efforts on the Kuroshio intrusion into the SCS were reviewed in this work.•Results of observation, laboratory, theoretical analyses, and a range of numerical model simulations were summarized.•Dynamical mechanisms controlling the Kuroshio intrusion into the SCS were discussed.•Several future research topics for gaining a better understanding of the Kuroshio intrusion are suggested. The Kuroshio carrying the northwestern Pacific water intrudes into the South China Sea (SCS) through the Luzon Strait, significantly affecting the temperature, salinity, circulation, and eddy generation in the SCS. Thus, the Kuroshio intrusion makes important contributions to the momentum, heat and salt budgets in the SCS. In the past decades, much work has been done on the Kuroshio intrusion. This paper reviews past efforts and summarizes our current understanding of the Kuroshio intruding processes from observational evidence, laboratory results, theoretical analyses, and a range of numerical model simulations. In addition, discrepancies between results simulated by models, as well as those between simulations and observations, are presented. Specifically, this paper addresses the following topics: (1) different types of the Kuroshio intrusion into the SCS and their identification, (2) vertical structure of the Kuroshio in the Luzon Strait, (3) an overview of the Luzon Strait transport resulting from observations and numerical model simulations, (4) seasonal and interannual variations of the Kuroshio intrusion, as well as eddy generation due to the Kuroshio path variation, and (5) dynamical mechanisms (e.g., wind forcing, interbasin pressure gradient, β effect and hysteresis, potential vorticity, eddy activity) controlling the Kuroshio intrusion into the SCS. Finally, several future research topics for gaining a better understanding of the Kuroshio intruding processes are suggested.